2005
DOI: 10.1111/j.1540-8183.2005.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Material‐Induced Renal Failure: An Overview

Abstract: The administration of iodinated contrast media (CM) is integral to many cardiovascular procedures. While it is clear that CM provide significant diagnostic benefit, there is some risk of contrast medium-related adverse events in a small percentage of patients. Potentially the most serious complication associated with the use of iodinated contrast agents is contrast-induced nephropathy (CIN). Most patients undergoing contrast-enhanced radiographic procedures are not at risk for CIN, however subjects with pre-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 65 publications
2
30
0
12
Order By: Relevance
“…The primary end point of this study was CIN defined as an increase in sCr of Ն0.5 mg/dl or Ն25% within 2 to 7 d of contrast administration (2,4,6,8,11,16). The secondary end point was the composite of either severe renal failure or death with renal failure as a contributing cause within 45 d. We followed patients for 45 d, using a combination of telephone and medical record review.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary end point of this study was CIN defined as an increase in sCr of Ն0.5 mg/dl or Ն25% within 2 to 7 d of contrast administration (2,4,6,8,11,16). The secondary end point was the composite of either severe renal failure or death with renal failure as a contributing cause within 45 d. We followed patients for 45 d, using a combination of telephone and medical record review.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…C ontrast-induced nephropathy (CIN) is a known complication of intravenous, iodinated contrast; is a common cause of renal failure in the inpatient setting (1)(2)(3)(4)(5); and is associated with both short-and long-term adverse outcomes (6,7). Previous reports indicated that CIN occurs in 4 to 20% of patients after intra-arterial administration after coronary angiography (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…CIN is a life-threatening dose-dependent reaction and is commonly defined as a decrease in renal function 24-48 hours after contrast media administration, with a rise in serum creatinine levels of more than 25% from the baseline (or an absolute increase greater than 0.5 mg/dL) three to five days after the procedure. [1][2][3][4][5][6][7][8][9] Preventative measures for CIN in cardiovascular procedures include pre-hydration, prophylactic administration of N-acetylcysteine and utilisation of iso-osmolar/hypo-osmolar contrast media. However, reducing the volume of contrast media within the procedure was found to be the most effective.…”
Section: Introductionmentioning
confidence: 99%
“…It is a transient and reversible form of acute kidney injury. However, the development of CIN is associated with a longer hospital stay, an increased morbidity, and mortality, in addition to a higher financial cost [6].Contrast-induced nephropathy (CIN) is a known complication of intravenous, iodinated contrast; It is a common cause of renal failure in the inpatient setting [6,[7][8][9][10]; and is associated with both short-and long-term adverse outcomes [11,12]. Previous reports indicated that CIN occurs in 4 to 20% of patients after intra-arterial administration after coronary angiography [13,14].…”
mentioning
confidence: 99%